Lonely Joy: How Families with Nonverbal Children with Disabilities Communicate, Collaborate, and Resist in a World that Values Words. Issue 2 (4th May 2019) - Raffety, Erin; Vollrath, Kevin; Harris, Emily; Foote, Laura
ABSTRACT: Drawing on ethnographic research with four families with children with profound cognitive disabilities who are nonverbal, this article argues that communication and joy among such families are undermined by common perceptions of disability as tragedy and lack of language as absence of communication. Because the Church often perpetuates understandings of disability as tragedy, joy in such families must stand in resistance to not just ableist society, but also to the Church. Therefore, we argue that both such families and the Church remain 'lonely' in their joy. Accordingly, we charge the Church to receive and accept a broad variety of communication in order to embrace, come alongside, and magnify the joy of families with persons with disabilities who are nonverbal, enlarging the context of joy in Christian community.